Singularity Theory 2007
DOI: 10.1142/9789812707499_0016
|View full text |Cite
|
Sign up to set email alerts
|

A Homological Approach to Singular Reduction in Deformation Quantization

Abstract: Abstract. We use the method of homological quantum reduction to construct a deformation quantization on singular symplectic quotients in the situation, where the coefficients of the moment map define a complete intersection. Several examples are discussed, among others one where the singularity type is worse than an orbifold singularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…The usage of invariant star products (and even better: invariant star products with a quantum momentum map) will hopefully allow also to treat the Morita theory of star products on singular quotients, see e.g. [6,29].…”
Section: G-actions On Symplectic Manifoldsmentioning
confidence: 99%
“…The usage of invariant star products (and even better: invariant star products with a quantum momentum map) will hopefully allow also to treat the Morita theory of star products on singular quotients, see e.g. [6,29].…”
Section: G-actions On Symplectic Manifoldsmentioning
confidence: 99%
“…In this paper, we apply the homological approach to singular reduction in deformation quantization developed in [13] to a model of gauge theory obtained via lattice approximation of Yang-Mills theory within the Hamiltonian approach. We refer to the classical paper [49] for the formulation of the full model (including matter fields) on a finite lattice and for its canonical quantization.…”
Section: References 50 1 Introductionmentioning
confidence: 99%
“…They proved that, under appropriate regularity properties of the group action, the BRST-procedure induces a star product on the reduced phase space. In [13], Bordemann, Herbig and Pflaum showed that this method may be extended to singular symplectic reduction, provided the following assumptions are fulfilled:…”
Section: References 50 1 Introductionmentioning
confidence: 99%
“…Batalin-Vilkovisky-Fradkin's method [11], [12] was proposed for gauge systems. In [8] the BRST method was developed based on the rather complicated homological construction including ghosts fields.…”
Section: Introductionmentioning
confidence: 99%